2021
DOI: 10.1155/2021/6615979
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of HBx Restrains Proliferation, Migration, and Invasion of HepG2 Cells

Abstract: Liver cancer is a major contributor to cancer-related death with poor survival for sufferers. Meanwhile, Hepatic B virus X protein (HBx) and XB130 are likely to participate in the pathogenesis of liver cancer. However, the detailed mechanism of HBx/XB130 in liver cancer remains to be further investigated. Our study explored the effects of HBx/XB130 on liver cancer progression. HBx and XB130 expression was detected by reverse transcription quantitative polymerase chain reaction (RT-qPCR) and Western blot. Overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The high-mobility group box transcription factor 1 (HBP1) has a tumor suppressor function. Cao et al [33] showed that HBP1 inhibits AFP by binding to the affinity site of the AFP promoter. Inhibition of AFP by HBP1 attenuated the effect of AFP on the protein levels of PTEN, matrix metallopeptidase 9 (MMP9) and cysteine-dependent aspartate-specific proteases-3 (caspase-3) in HCC cells.…”
Section: Hbv-infected Hepatocytes Preferentially Express Alpha-fetopr...mentioning
confidence: 99%
“…The high-mobility group box transcription factor 1 (HBP1) has a tumor suppressor function. Cao et al [33] showed that HBP1 inhibits AFP by binding to the affinity site of the AFP promoter. Inhibition of AFP by HBP1 attenuated the effect of AFP on the protein levels of PTEN, matrix metallopeptidase 9 (MMP9) and cysteine-dependent aspartate-specific proteases-3 (caspase-3) in HCC cells.…”
Section: Hbv-infected Hepatocytes Preferentially Express Alpha-fetopr...mentioning
confidence: 99%
“…Hepatitis B virus X protein (HBx) has been found to be overexpressed in liver cancer tissues. 492 It acts as a transcriptional co-activator through direct interaction with various proteins, such as the TATA-binding protein, RPB5 subunit of RNA polymerase II, TF IIH, TF IIB, and the proteins of basic domain-leucine zipper (bZIP) family, including the cyclic AMP-response element (CRE)-binding protein (CREB). 493 HBx interacts with the co-activators CBP/p300 and cooperates with CBP/p300 in the CREB-mediated activation.…”
Section: Diseases Associated With Mutation Of Transcription Co-activa...mentioning
confidence: 99%
“…Zhou et al proposed that the HBV X protein captures protons and chloride ions and induces collagen expression in the liver, forming strong hydrogen bonds with the captured protons, and that the HBV X protein and collagen locally accumulate HCl, triggering cirrhosis in some patients The disease progresses to liver cancer ( Zhou et al, 2017 ). HBx can modulate biological processes in HepG2 cells and accelerate the development of HCC by activating the XB130-mediated phosphatidylinositol 3-kinase (PI3K)/AKT pathway ( Huang et al, 2021 ). HBx increases the expression of Smad-interacting protein 1 (SIP1) and recruits it to the promoter of E-cadherin to repress the transcription of E-cadherin, and the consequent decrease in E-cadherin expression blocks intercellular adhesion and attachment, thereby promoting tumor invasiveness ( Ye et al, 2019 ).…”
Section: Pathogenic Factorsmentioning
confidence: 99%